In vitro effects of mechanical stimulation and photobiomodulation on osteoblastic cell function: A proof of concept study. Issue 1 (April 2017) - Chintavalakorn, Rochaya; Khantachawana, Anak; Viravaidya-Pasuwat, Kwanchanok; Santiwong, Peerapong; Surarit, Rudee
Abstract: Background: The effect of mechanical stimulation and photobiomodulation on tissue defect restoration has recently been investigated in various fields of tissue engineering such as acceleration of healing process and bone calcification. Mechanical stimulation generates shear stress on bone cells resulting in promotion of bone formation whereas photobiomodulation regulates inflammation, decreases pain, accelerates cell proliferation and enhances healing. Methods: MC3T3-E1 cells were cultured in 3 dimensional collagen scaffolds. Cells were daily stimulated by either mechanical loading of 3 Hz sinusoidal with 3000 μstrain vibration, or photobiomodulation using LED with 3 J/cm 2 fluency or combination of both. The calcifications of 3D tissue-engineered bones were examined by non-destructive monitoring device every day for 42 days. Results: The 3D tissue-engineered bones that exposed to mechanical alone or combined stimulation exhibited early calcification, higher calcium content and bulk density comparing to control and light stimulation alone. Furthermore, the mRNA expression level of bone formation related genes such as RUNX2, ALP, osteopontin and osteocalcin were examined 7 days after stimulations. We showed the potential upregulation of ALP gene after mechanical stimulation alone or combined with light treatment. On day 28 Von Kossa stain revealed higher calcium deposition and increased cell migration to the deeper zone of 3D tissue-engineered bones. Conclusion: We suggested that the mechanical treatment alone and combination with light treatment could accelerate the calcification of 3D tissue-engineered bone possibly through up-regulation of ALP gene during early stage of bone formation.